Time delay systems : theory, numerics, applications, and experiments - Insperger, T.; Ersal, Tulga; Orosz, Gábor (Springer, 2017)
This volume collects contributions related to selected presentations from the 12th IFAC Workshop on Time Delay Systems, Ann Arbor, June 28-30, 2015. The included papers present novel techniques and new results of delayed dynamical systems. The topical spectrum covers control theory, numerical analysis, engineering and biological applications as well as experiments and case studies. The target audience primarily comprises research experts in the field of time delay systems, but the book may also be beneficial for graduate students alike.
Keywords: Time delay systems.; elektronické knihy; electronic books